Formulation Development Studies on Enhancement of Solubility and Dissolution Rate of Etoricoxib by Cyclodextrin Complexation - Chowdary, K.P.R.; Venkata Reddy, M. (Asian Journal of Chemistry, 2010)
The objective of the study is to evaluate the feasibility of employing cyclodextrin complexation for enhancing the solubility and dissolution rate of etoricoxib, a poorly soluble drug belonging to BCS-class II. The feasibility of formulating cyclodextrin complexes of etoricoxib into compressed tablets with enhanced dissolution rate was also investigated. Phase solubility studies indicated that the aqueous solubility of etoricoxib was linearly increased as a function of cyclodextrin concentration and formation of 1:1 M complexes of etoricoxib and cyclodextrins in solution with a stability constant (KC) of 109 and 170 M -1 with b-cyclodextrin andb-cyclodextrin, respectively. Etoricoxib-cyclodextrin complexes prepared byb-Cyclodextrin and hydroxypropyl-b-cyclodextrin gave, respectively 133 fold and1) of etoricoxib at 1:3 ratio of drug:cyclodextrin.b-cyclodextrin and hydroxypropyl-b-cyclodextrin, respectively gave 5.2 and 2.291) in wet granulation method and 13.28 and 5.31 fold hydroxypropyl- kneading method gave rapid and higher dissolution of etoricoxib when compared to etoricoxib pure drug. 166 fold increase in the dissolution rate (K Etoricoxib (60 mg) tablets were prepared employing drug-cyclodextrin (1:3) complexes by wet granulation and direct compression methods and were evaluated. Etoricoxib tablets formulated employing fold increase in the dissolution rate (K increase in direct compression method when compared to plain tablets. Etoricoxib-cyclodextrin complexes could be formulated in to compressed tablets retaining their enhanced dissolution rate characteristics. Thus, cyclodextrin complexation is recommended as an effective and efficient technique for enhancing the solubility and dissolution rate of etoricoxib from tablets.